More Than Meets the Eye? The Role of Annual Ornamental Flowers in Supporting Pollinators. Issue 1 (22nd November 2019) - Erickson, E; Adam, S; Russo, L; Wojcik, V; Patch, H M; Grozinger, C M
Abstract: Ornamental flowers are commonly planted in urban and suburban areas to provide foraging resources for pollinator populations. However, their role in supporting broad pollinator biodiversity is not well established as previous studies have been conducted in urban landscapes with pollinator communities that are distinct from those in natural systems. We observed pollinator visitation patterns to five ornamental annual plant genera and their cultivars over multiple years at two semi-natural sites in Pennsylvania to understand their potential for supporting diverse pollinator communities. There was significant variation in visitor abundance and diversity by season and year for many annual ornamental cultivars. Within some genera, cultivars had similar visitor abundance, diversity, and main visitor taxa, while cultivars in other genera varied greatly in these measures. We observed only polylectic (pollen generalist) bee species visiting annual ornamentals, despite the presence of oligolectic (pollen specialist) bee species in the background population. We conclude that the attractiveness of annual ornamental plants likely depends on both cultivar characteristics and environmental context. While their role in supporting complex pollinator populations is limited both based on the number of and dietary breadth of the species they support, ornamental plants may nonetheless provide long-lasting supplemental foraging resources for the generalist pollinator communities characteristic of urban and suburban environments.